FROM MOON TO COMET LANDING: RE-IMAGINING (SCIENTIFIC) MEDIA EVENTS IN THE AGE OF TWITTER - Rossi, Luca (AoIR Selected Papers of Internet Research, 2015)
The relevance of Twitter data for research has grown exponentially in fields from communication studies to political analysis - not to mention the huge success in physics and networks studies. While Twitter data have undoubtedly contributed to the emergence of new interdisciplinary research efforts, we believe that a more thorough reflection on the nature of Twitter data and its access practices is necessary. In this contribution we will consider three open problems that, if not answered, may undermine credibility of Twitter as a viable data source for future research. We will discuss Twitter data and Twitter research focusing on three main questions: 1) To what extend can we consider twitter a proxy of social life? What are the necessary assumptions of this? 2) How is it possible to study Twitter data if Twitter as a socio-technical platform shows a highly unstable nature? 3) What are the consequences of the doing research based on privately-owned data? We will conclude the paper questioning the real relevance of Twitter research and asking to what extend data-availability generated the huge success of Twitter research.